Pengaruh Terapi Tertawa terhadap Tingkat Kemarahan pada Pasien Perilaku Kekerasan di Wilayah Kerja Puskesmas Dukuhturi Kabupaten Tegal - Evi Supriatun; Alfiyah Nur Baeti; Nafisah Itsna Hasni; Robieth Sohiburoyyan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
The research was conducted to implement laughter therapy to reduce anger levels in patients with violent behavior disorders. Methodology: This was a descriptive analytical study with a case study approach. The subjects were people with mental disorders. Data obtained through interviews, observation, and physical examination. Those were presented in the form of a narrative text and a frequency distribution table. Result: The levels of anger before being given laughter therapy in patient 1 and 2 were 20 and 22. After the therapy for 3 days the score in patient 1 decreased by 7 while patient 2 became 7 in the low category. Recommendation: Patients with violent behavior should be given laughter therapy to reduce the anger.